Identification of Plankton on Fish Pond of Oreochromis niloticus Infected by Viral Nervous Necrosis - Uun Yanuhar; Muhammad Musa; Dyah Tri Rahayu; Diana Arfiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2016)
The purpose of study is to determine the type of plankton found in cultivation pond of nile tilapia infected by VNN. The method is to identify the plankton in the water pond and testing the VNN that infects nile tilapia related to plankton eaten using Polymerase Chain Reaction (PCR). VNN identification results on the nile tilapia digestive tract stomach and intestines as well as plankton found in the stomach and intestines indicate VNN positively. Plankton found in the digestive tract of fish is division of Chlorophyta, Bacillariophyta, phylum Rotifera and Crustacea. It indicates that nile tilapia infected by VNN both on the gastrointestinal tract organs, stomatch or intestines and plankton were found with positive VNN digestive duct, while plankton found in water pond is VNN negative. The VNN infection depends on the nature of specifications VNN on nile tilapia and the plankton in the nile tilapia digestive duct.